2017
DOI: 10.15376/biores.12.2.2433-2451
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evaluation of a Timber Construction Element Originating from the Great Metéoron Monastery in Greece

Abstract: This study identified the wood species and evaluated the degree of weathering and biological degradation of a historical timber construction element originating from the Great Metéoron monastery in Metéora, Greece. The wood material was provided from the interior side of a balcony that was fully covered with a roof and exposed to outdoor conditions for more than 400 years. The species was identified as Quercus spp. of the white oak group. In the timber element, the physical, morphological, and chemical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Table 1 explains control wood peaks. The peaks were compared with the results of other studies [11,[42][43][44][45]. Interestingly, there were some differences in the spectral bands observed in this study from those reported earlier.…”
Section: Changes In Cell Wall Chemistrymentioning
confidence: 58%
“…Table 1 explains control wood peaks. The peaks were compared with the results of other studies [11,[42][43][44][45]. Interestingly, there were some differences in the spectral bands observed in this study from those reported earlier.…”
Section: Changes In Cell Wall Chemistrymentioning
confidence: 58%
“…The fungal-decayed beech wood IR spectra corresponded to the relative intensities of aromatic skeletal vibrations against the typical bands for carbohydrates ( Table 3 ). The peak at 1504 cm −1 was used as a reference peak for lignin, and the ratio between this peak and the carbohydrate-related peaks at 1732 cm −1 , 1367 cm −1 , 1155 cm −1 , and 895 cm −1 was used as a measure of decay [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Madhoushi (2016) reported that the wood species of structural elements removed from a historical building in Gorgan, Iran were identified as elm, lime tree, oak, sugar maple and scots pine. Dogu et al (2017) determined that the wood of a very old timber building element that was used on the inside of a balcony and exposed to outdoor conditions for more than 400 years belongs to oak wood. They also stated that oak wood species is characterized by high durable heartwood since it contains high amount of tannins.…”
Section: Wood Identificationmentioning
confidence: 99%